Clinical, radiological, and genetic characterization of SLC13A5 variants in Saudi families: Genotype phenotype correlation and brief review of the literature - AlQudairy, Hanan; AlDhalaan, Hesham; AlRuways, Sarah; AlMutairi, Nouf; AlNakiyah, Maha; AlGhofaili, Reema; AlBakheet, Albandary; Alomrani, Adeeb; Alharbi, Omar A.; Tous, Ehab; AlSayed, Moeen; AlZaidan, Hamad; et al. (Frontiers in Pediatrics, 2023)
Background: SLC13A5 (solute carrier family 13, member 5) encodes sodium/citrate cotransporter (NaCT) which mainly localizes in cellular plasma membranes in frontal cortex, retina, and liver. Pathogenic variants of the gene cause an autosomal recessive syndrome known as “developmental and epileptic encephalopathy 25 with amelogenesis imperfecta”. Results: Here, we have investigated six patients from three different consanguineous Saudi families. The affected individuals presented with neonatal seizures, developmental delay, and significant defects in tooth development. Some patients showed other clinical features such as muscle weakness, motor difficulties, intellectual disability, microcephaly, and speech problems in addition to additional abnormalities revealed by electroencephalograms (EEGs). To diagnose and study the genetic defects of the patients, whole-exome sequencing (WES) coupled with confirmatory Sanger sequencing was utilized. Iterative filtering identified two variants in SLC13A5, one of which is novel, in the families. Family 1 and 2 had the same insertion (a previously reported mutation) leading to frameshift and premature stop codon. The third family had a novel splice site variant. Confirmatory Sanger sequencing corroborated WES results and indicated full segregation of the variants in the corresponding families. The patient's conditions were poorly controlled by multiple anti-epileptics as they have needed constant care. Conclusion: Considering that recessive mutations are more common in the Arab population, SLC13A5 screening should be prioritized in future patients harboring similar symptoms including defects in molar development.